Application of modified porcine xenograft by collagen coating in the veterinary field: pre-clinical and clinical evaluations - Jo, Hyun Min; Jang, Kwangsik; Shim, Kyung Mi; Bae, Chunsik; Park, Jung Bok; Kang, Seong Soo; Kim, Se Eun (Frontiers in Veterinary Science, 2024)
This study aimed to identify a collagen-coating method that does not affect the physicochemical properties of bone graft material. Based on this, we developed a collagen-coated porcine xenograft and applied it to dogs to validate its effectiveness. Xenografts and collagen were derived from porcine, and the collagen coating was performed through N-ethyl-N′-(3-(dimethylamino)propyl) carbodiimide/N-hydroxysuccinimide (EDC/NHS) activation. The physicochemical characteristics of the developed bone graft material were verified through field emission scanning electron microscope (FE-SEM), brunauer emmett teller (BET), attenuated total reflectance-fourier transform infrared (ATR-FTIR), and water absorption test. Subsequently, the biocompatibility and bone healing effects were assessed using a rat calvarial defect model. The physicochemical test results confirmed that collagen coating increased bone graft materials' surface roughness and fluid absorption but did not affect their porous structure. In vivo evaluations revealed that collagen coating had no adverse impact on the bone healing effect of bone graft materials. After confirming the biocompatibility and effectiveness, we applied the bone graft materials in two orthopedic cases and one dental case. Notably, successful fracture healing was observed in both orthopedic cases. In the dental case, successful bone regeneration was achieved without any loss of alveolar bone. This study demonstrated that porcine bone graft material promotes bone healing in dogs with its hemostatic and cohesive effects resulting from the collagen coating. Bone graft materials with enhanced biocompatibility through collagen coating are expected to be widely used in veterinary clinical practice.